Design, techno-economic and environmental risk assessment of aero-derivative industrial gas turbine - Abaad, Abdelmanam (Cranfield University, 2012)
Increased availability of natural gas has boosted research and development efforts to further increase gas turbine performance. Performance has been increased remarkably and unit cost reduced due to achievements gained in improving thermodynamic cycles and cooling technologies. However, increased complexity in power industry regulations and fluctuations in fuel price have indicated that all the aforementioned improvements in gas turbine performance could not cope with the increased competition in the gas turbine industrial market. Innovation within the aero-derivative concept has enabled further significant improvement in the performance of industrial gas turbines. It allows a more beneficial approach than developing new designs of industrial gas turbines owing to reduced designing time and cost. Objectives in this project focus on developing a methodology of design and assessing aeroderivative gas turbine engines derived from a 130-seat aircraft engine. Developed methodology includes techno-economic and environmental assessment, conducted through further developments of models based on Techno-economic and Environmental Risk Assessment (TERA) philosophy, to be applied in further industrial applications. Tools used in this investigation include a significant literature research on the development of aero-derivative gas turbine technologies, including thermodynamic cycles and its land-based applications. Turbomatch is a homebased code developed in Cranfield University, used in calculating design point and predicting off-design performance of parent aero-engine and the aeroderivative engines developed. Excel and FORTRAN code are also used in calculating engine’s design parameters, and creating a model of life estimation Creep. Moreover, FORTRAN code is used for building emission and economic models for power generation and combined heat and power applications. Finally, MATLAP code is used in creating a small model for generating performance TXT files, and running marine integrated models platform. All models needed to develop the methodology have been created, and calculations of an engine’s performance and assessment were conducted based on this developed methodology. Sensible results are generated from the investigated methodology and they show acceptable designs of aero-derivative engines on different thermodynamic cycles. Based on the acceptable level of technology and material thermal barriers, all design and off-design performance limitations of new developed aero-derivative engines have been determined for a wide range of ambient conditions. Techno-economic and environmental assessment performed through implementing the developed aero-derivative engines on power generation and marine applications under different operating scenarios. Results of operating the engines on power generation and marine applications have been investigated and compared. It is observed that engines respond differently when operating under different environmental profiles, depending on the number of units engaged and their thermodynamic cycle as well as mechanical configurations. Also, the selected specific gas turbine engine can be the best economical choice for operating on determined scenario, while it cannot be when operating in different scenarios. Assessment of developed engines on the investigated application shows how the lowest specific cost (small engine size) can constitute important criteria in engine selection.
Keywords: Cycles; Design; Performance; Derivation; Development; Conditions; Limitations; Emission; Creep; Economics; PG; Marin; Assessment